2018
DOI: 10.1111/vde.12517
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects of intralymphatic immunotherapy (ILIT) on canine atopic dermatitis

Abstract: ILIT is safe and feasible, and provides long-lasting relief in some atopic dogs with a limited number of injections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 29 publications
4
39
1
3
Order By: Relevance
“…Intralymphatic immunotherapy in dogs was first reported more than 30 years ago, when some dogs not responding to conventional immunotherapy improved with the allergen extract administered intralymphatically. Recently, intralymphatic immunotherapy (Figure ) with alum‐precipitated allergens was reported in dogs with a comparable efficacy to conventional immunotherapy . Well‐powered, double‐blind and randomized studies evaluating intralymphatic immunotherapy are needed.…”
Section: Intralymphatic Immunotherapy (Ilit)mentioning
confidence: 99%
“…Intralymphatic immunotherapy in dogs was first reported more than 30 years ago, when some dogs not responding to conventional immunotherapy improved with the allergen extract administered intralymphatically. Recently, intralymphatic immunotherapy (Figure ) with alum‐precipitated allergens was reported in dogs with a comparable efficacy to conventional immunotherapy . Well‐powered, double‐blind and randomized studies evaluating intralymphatic immunotherapy are needed.…”
Section: Intralymphatic Immunotherapy (Ilit)mentioning
confidence: 99%
“…4,5 For many years ASIT has been administered to dogs subcutaneously (SCIT) using aqueous or aluminium-precipitated solutions of allergens. In the last few years, alternative routes of administration have been evaluated including intralymphatic (ILIT), [12][13][14] sublingual (SLIT) 10,11 and epicutaneous immunotherapy. 15 Intralymphatic immunotherapy has been reported to be safe and equal in efficacy to SCIT; preliminary results have shown that response to treatment may occur more quickly than for SCIT.…”
Section: Introductionmentioning
confidence: 99%
“…15 Intralymphatic immunotherapy has been reported to be safe and equal in efficacy to SCIT; preliminary results have shown that response to treatment may occur more quickly than for SCIT. 13,14 Sublingual immunotherapy has been reported to be safer than SCIT and may present a practical treatment option for owners who are reluctant to administer subcutaneous injections. 16 Comparison of the different treatment options for cAD in prospective studies has not been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…First, to reflect difficulty in achieving clinical control in each case, a treatment score was created to evaluate the extent of chosen medical therapy. The scoring system was adapted for retrospective purposes from systems previously reported for atopic dermatitis . A few drugs were added to this scheme (azathioprine, leflunomide) and all doses were scored as the maximum dose that each dog received (Table ).…”
Section: Methodsmentioning
confidence: 99%